Relationship between cultural diversity awareness and achievement motivation of medical students at the undergraduate level in Pakistan - Fatima, Fozia; Ali, Sabir; Siddiqi, Fuad Ahmad; Sadiq, Naushaba (Frontiers in Education, 2024)
This study investigates the relationship between cultural diversity awareness and achievement-oriented goals among undergraduate medical students at the university level. Utilizing the Achievement Motivation Model by McInerney et al. (2003) and the General Fulfillment Aims Orientation Scale (GAGOS), it examines mastery, performance, and social goals. Additionally, it incorporates Ennejar's (2021) cultural diversity awareness model to assess students' attitudes toward cultural diversity. Data were collected from 80 final-year MBBS students through a survey and analyzed using SPSS for descriptive and inferential statistics. Results show that students have a high level of cultural diversity awareness and recognize biases, supporting diverse voices and cultural differences. A significant positive correlation (r = 0.948, p < 0.05) between cultural diversity awareness and achievement motivation was found, although no significant differences were observed based on gender or age. These findings suggest that enhancing personal development, altruism, and social recognition may boost motivation and that diversity and inclusion programs are crucial for fostering environments that promote achievement motivation.